2007
DOI: 10.1126/science.1132912
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Identification of Mendel's I Locus

Abstract: A key gene involved in plant senescence, mutations of which partially disable chlorophyll catabolism and confer stay-green leaf and cotyledon phenotypes, has been identified in Pisum sativum, Arabidopsis thaliana, and Festuca pratensis by using classical and molecular genetics and comparative genomics. A stay-green locus in F. pratensis is syntenically equivalent to a similar stay-green locus on rice chromosome 9. Functional testing in Arabidopsis of a homolog of the rice candidate gene revealed (i) senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
178
2
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 180 publications
(186 citation statements)
references
References 5 publications
1
178
2
5
Order By: Relevance
“…Recently, the mutation of Mendel's I locus was elucidated molecularly . In contrast to an earlier finding of reduced SGR gene expression in the mutant (Armstead et al, 2007), gene expression was found to be normal. By complementing a rice sgr mutant with rice SGR gene exhibiting a 6-bp-insertion, it was concluded that the analogous mutation present in Mendel's green pea SGR gene abolished SGR function .…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Recently, the mutation of Mendel's I locus was elucidated molecularly . In contrast to an earlier finding of reduced SGR gene expression in the mutant (Armstead et al, 2007), gene expression was found to be normal. By complementing a rice sgr mutant with rice SGR gene exhibiting a 6-bp-insertion, it was concluded that the analogous mutation present in Mendel's green pea SGR gene abolished SGR function .…”
Section: Introductioncontrasting
confidence: 99%
“…The Columbia (Col-0) ecotype of Arabidopsis (Arabidopsis thaliana) was used as wild type. For silencing of AtSGR1 by RNA interference, a pHannibal-derived construct as described in Armstead et al (2007) was used. pao1 was transformed by a floral dip method and homozygous pao1 atsgr1i lines selected by kanamycin resistance.…”
Section: Plant Materials and Senescence Inductionmentioning
confidence: 99%
See 3 more Smart Citations